Can an Emission Trading Scheme really reduce CO2 emissions in the short term? Evidence from a maritime fleet composition and deployment model. (September 2019) - Gu, Yewen; Wallace, Stein W.; Wang, Xin
Highlights: The new model integrates the fleet composition and deployment problem and METS. In most scenarios, METS cannot guarantee CO2 emission reduction in the short term. In some cases, regional METS can even increase overall CO2 emission of the fleet. A global scheme works better than a regional one in terms of emission reduction. METS has better emission reduction in a low-fuel-price scenario. Abstract: Global warming is a major challenge for this planet, and its solution requires efforts throughout society. Maritime transportation, which carries more than 90% of the global trade, plays a critical role in the contribution of greenhouse gas (GHG) emissions. However, the GHGs emitted by the global fleet still fall outside the emission reduction scheme established by the Kyoto Protocol. Alternative solutions are therefore sought. Several market-based measures have been proposed and submitted to IMO for discussion and evaluation. In this paper, we focus on one of these measures, namely the Maritime Emissions Trading Scheme (METS). An optimization model that integrates (global or regional) METS into the classical fleet composition and deployment problem is proposed. This model is used as a tool to study the impact of METS on fleet operations and their CO2 emissions. The results of the computational study suggest that, in the short term, the implementation of METS does not lead to emission reduction in most scenarios. However, in the case of low bunker prices, high allowance costs or global METS coverage, a more significant CO2 decrease in the short term can be expected.